Предмет: Алгебра,
автор: bawrinnazar
Решите уравнение :
log(3)x-log(3)(x²-6)=0
Ответы
Автор ответа:
0
Х=-2 не подходит
Ответ 3
Ответ 3
Приложения:
Автор ответа:
0
log(3)x - log(3)(x^2 - 6) = 0
log(3)x = log(3)(x^2 - 6)
x = x^2 - 6, x > 0
x^2 - x - 6 = 0, x > 0
По теореме Виета:
x = -2 и 3, х > 0
х = 3
log(3)x = log(3)(x^2 - 6)
x = x^2 - 6, x > 0
x^2 - x - 6 = 0, x > 0
По теореме Виета:
x = -2 и 3, х > 0
х = 3
Похожие вопросы
Предмет: Физика,
автор: kvv20070305
Предмет: Английский язык,
автор: vanektsur221
Предмет: Физика,
автор: ioleksenko2
Предмет: Химия,
автор: ymnichka89899
Предмет: Химия,
автор: Диана3851